DIVERSITY OF BACTERIA IN SEDIMENT FROM MANGROVE AND BEKANTAN CONSERVATION AREA (KKMB) IN TARAKAN CITY - Yulma Yulma; Gloria Ika Satriani; Awaludin Awaludin; Burhanuddin Ihsan; Bella Pratiwi (AQUASAINS, 2019)
Bacteria in sediment plays an important role in various biochemical processes in the waters area, for instance degradation of organic matter, biogeochemical cycle, controlling ammonium, nitrates and nitrites concentration, food source for fauna, primary production, and pollution remediation. The purpose of this study was to determine the diversity of bacteria (Genus) in sediment on the Mangrove and Bekantan Conservation Area (KKMB), Tarakan City. The method used was explorative descriptive method with genus identification as parametric test. Bacterial identification parameters were tested using Gram-test, main test and further test was carried out at the Laboratory of Fish Quarantine, Quality Control and Safety Fishery Products Class II Tarakan. The bacteria found in the sediments on the KKMB were 16 genera i.e. Enterobacteria, Eubacterium, Listeria, Actinobacillus, Bacteriodes, Streptococcus, Plesiomonas, Corynebacterium, Pseudomonas, Aeromonas, Bordetella parapertussis, Micrococcus, Staphylococcus, Clostridium, Neisseria, and the dominant numbers found was Bacillus.